2011
DOI: 10.1073/pnas.1103660108
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of an unusual biosynthetic origin for circular proteins in legumes

Abstract: Cyclotides are plant-derived proteins that have a unique cyclic cystine knot topology and are remarkably stable. Their natural function is host defense, but they have a diverse range of pharmaceutically important activities, including uterotonic activity and anti-HIV activity, and have also attracted recent interest as templates in drug design. Here we report an unusual biosynthetic origin of a precursor protein of a cyclotide from the butterfly pea, Clitoria ternatea, a representative member of the Fabaceae p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
192
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(195 citation statements)
references
References 37 publications
2
192
1
Order By: Relevance
“…PA1b and Cter M, the insecticidal part of the PA1 gene, appear to act via distinct mechanisms. In common with other cyclotides, Cter M binds membranes and forms pores (4). In contrast, our work shows that the PA1b peptide acts specifically via a membranous receptor.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…PA1b and Cter M, the insecticidal part of the PA1 gene, appear to act via distinct mechanisms. In common with other cyclotides, Cter M binds membranes and forms pores (4). In contrast, our work shows that the PA1b peptide acts specifically via a membranous receptor.…”
Section: Discussioncontrasting
confidence: 50%
“…Very few known molecules are really able to provide alternative solutions to chemical pesticides; plant insecticidal molecules either target digestive enzymes or are chitin-binding proteins (4). Thus, the inhibition of V-ATPase in the midgut of insects represents a new target for a bioinsecticide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nature of the residue in the P1 position immediately upstream of the cyclotide domain is probably not important; it can be a Lys, as in the O. affinis cyclotides, or an Asn as occurs in other cyclotide subfamilies, as long as the Ntr is surfaceexposed and accessible to proteases and cleavage at this junction prior to the cleavage at the Ctr that results in cyclization. This is supported by the recent discovery of cyclotides in the Fabaceae family where the cyclotide domain is directly preceded by the ER signal peptide and the Ntr is absent (20). The cleavage of this signal peptide in the ER would free up the N terminus of the cyclotide, which presumably remains free until the cyclotide precursor reaches the compartment where cyclization occurs.…”
Section: Discussionmentioning
confidence: 52%
“…The importance of the P2Ј residue within the Ctr was exemplified with the truncation mutants that showed that Leu is essential for cyclization and this is not entirely surprising as a Leu in this position is completely conserved across all cyclic peptides found in all species except the Fabaceae, which contain an Ile (20). Cleavage and cyclization occurs 2 amino acids from this leucine.…”
Section: Discussionmentioning
confidence: 99%